Effect of high altitude on human postprandial 13C‐octanoate metabolism, intermediary metabolites, gastrointestinal peptides, and visceral perception. Issue 3 (2nd August 2021) - Strunz, Patrick‐Pascal; Vuille‐dit‐Bille, Raphael N.; R. Fox, Mark; Geier, Andreas; Maggiorini, Marco; Gassmann, Max; Fruehauf, Heiko; Lutz, Thomas A.; Goetze, Oliver
Abstract: Objective: At high altitude (HA), acute mountain sickness (AMS) is accompanied by neurologic and upper gastrointestinal symptoms (UGS). The primary aim of this study was to test the hypothesis that delayed gastric emptying (GE), assessed by 13 C‐octanoate breath testing (OBT), causes UGS in AMS. The secondary aim was to assess post‐gastric mechanisms of OBT, which could confound results under these conditions, by determination of intermediary metabolites, gastrointestinal peptides, and basal metabolic rate. Methods: A prospective trial was performed in 25 healthy participants (15 male) at 4559 m (HA) and at 490 m (Zurich). GE was assessed by OBT (428 kcal solid meal) and UGS by visual analogue scales (VAS). Blood sampling of metabolites (glucose, free fatty acids (FFA), triglycerides (TG), beta‐hydroxyl butyrate (BHB), L‐lactate) and gastrointestinal peptides (insulin, amylin, PYY, etc.) was performed as well as blood gas analysis and spirometry. Statistical analysis: variance analyses, bivariate correlation, and multilinear regression analysis. Results: After 24 h under hypoxic conditions at HA, participants developed AMS ( p < 0.001). 13 CO2 exhalation kinetics increased ( p < 0.05) resulting in reduced estimates of gastric half‐emptying times ( p < 0.01). However, median resting respiratory quotients and plasma profiles of TG indicated that augmented beta‐oxidation was the main predictor of accelerated 13 CO2 ‐generation under these conditions. Conclusion: Quantification of 13 C‐octanoate oxidation by a breath test is sensitive to variation in metabolic (liver) function under hypoxic conditions. 13 C‐breath testing using short‐chain fatty acids is not reliable for measurement of gastric function at HA and should be considered critically in other severe hypoxic conditions, like sepsis or chronic lung disease. Abstract : The 13 C‐octanoate breath test was validated as a gastric emptying test for solid meals by quantification of the 13 C/12 C isotopic ratio in exhaled CO2 . The 13 C‐labeled test meal is emptied from the stomach as the rate‐limiting step and the post‐absorptive metabolism of the 13 C‐labeled short‐chain fatty acid is assumed as constant. This study found that gastric emptying in healthy participants under hypoxic conditions (4559 m) was accelerated by variation in metabolic (liver) function.